A Guide to Responsible Research - Marusic, Ana (Collaborative Bioethics, 2023)
This Open Access book is a guide to good, responsible research at each step of the process of research discovery, so that a researcher at the beginning of a scientific career has a clear pathway to doing good research and producing reliable results. The textbook will give context to the practices described in the European Code of Conduct for Research Integrity, guided by the fundamental principles or research integrity - reliability, honesty, respect, and accountability. Although we base the book on the European Code, the principles are the same in the global research community, such as those outlined in Fostering Integrity in Research from the US National Academies; Engineering and Medicine. The chapters in the book follow good research practices, give practical advice and address basic principles. In this way, the book is applicable to different research fields. It directs readers to various sources for further and updated information, particularly drawing from the resources available at The Embassy of Good Science, the European platform for research integrity and ethics.